Model Internalisasi Nilai Anti-Korupsi Melalui Pengajaran di Perguruan Tinggi (Studi Kasus Fakultas Pendidikan Agama Islam Universitas Singgaperbangsa Karawang) - Rosadi, Dede; Syafri, Ulil Amri; Hafidhuddin, Didin; Beik, Irfan Syauqi (Ta’dibuna: Jurnal Pendidikan Islam, 2015)
Corruption in Indonesia is very worrying. On the other hand, the efforts to combat corruption have not shown optimal results. On one side, there is the law on corruption, but on the other hand corruption persists. One of the efforts taken is through education that is considered strategic for prevention. Based on the decision letter of Kopertais Region II of West Java and BantenNo.002/Kep.II/SK-1/IX/2011, the Facultyof Islamic Studies of Singaperbangsa State University of Karawang taken anti-corruption education courses as a compulsory subject. The focus of the problem in this study is internalization modelof Anti-corruption value in Faculty of Islamic Studies of Singaperbangsa State University of Karawang. The specific aim of this study is to have a concept of internalization model of anti-corruption value through teaching in Islamic Higher Education properly and appropriately. The general aim of this study is to have a concept of internalization model of anti-corruption with Islamic worldview basic which can be implemented in Islamic Higher Education. The method used in this research is to use the mixed method, a combination of qualitative and quantitative approaches. The firstmethod is qualitative descriptive approach, it was taken because this study used interviews, observation, and documentation as the primary data source. The quantitative data was analyzedusing descriptive statistic with the technique of SEM (Structural Equation Modelling) application and validity test. Results of research on the anti-corruption lessons in Faculty of Islamic Studies shows that learning activities are held is limited to the transfer of the knowledge (cognitive). It yet emphasis on character formation (affective) and the moral consciousness in the resistance (psychomotor) against corruption. Model internalization of effective Anti-Corruption will appear if the learning patterns lead to pattern formation of student habits (habit formation) and modelling (role model). In addition, the model also should include learning objectives aimed at the establishment of Anti-corruption personality on students’ personal and the applicationofAnti-corruption values in daily activities of life. The subject matter of the Anti-corruption education directed at theori of Hubud Hazards associated with the world, ascetic morality and honest or trustworthy. Methods and techniques used Qudwah learning and habituation. Evaluation of learning techniques directed at non-verbal and writing of the absorption of the material (matter avoid memorizing concepts or more materials are digging of opinion) and affective tests. Tests were carried out on a model of internalization of Anti-corruption shows the evidence of the questionnaire with an average positive impact and significance of 75% and 25% are influenced by other variables. Therefore, based on the research that the model can be used with various limitations Keyword: Anti korupsi, internalisasi nilai, perguruan tinggi